A Glutamine-Rich Factor Affects Stem Cell Genesis in Leech - Kristi A. Hohenstein; Shirley A. Lang; Tej Nuthulaganti; Daniel H. Shain (Stem Cells International)
Leech embryogenesis is a model for investigating cellular and molecular processes of development. Due to the unusually large size of embryonic stem cells (teloblasts: 50–300 μm) in the glossiphoniid leech, Theromyzon tessulatum, and the presence of identifiable stem cell precursors (proteloblasts), we previously isolated a group of genes upregulated upon stem cell birth. In the current study, we show that one of these genes, designated Theromyzon proliferation (Tpr), is required for normal stem cell genesis; specifically, transient Tpr knockdown experiments conducted with antisense oligonucleotides and monitored by semiquantitative RT-PCR, caused abnormal proteloblast proliferation leading to embryonic death, but did not overtly affect neuroectodermal or mesodermal stem cell development once these cells were born. Tpr encodes a large glutamine-rich (∼34%) domain that shares compositional similarity with strong transcriptional enhancers many of which have been linked with trinucleotide repeat disorders (e.g., Huntington's).